Promoting societal resilience during the COVID-19 pandemic: a multi-country analysis of public health strategies - D'Amelio, Anna Carole; Cataldi, Sarah; Dallagiacoma, Giulia; Gentile, Leandro; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Enhancing public health communication during a global crisis is crucial to promote resilience. This study examines the influence of health communication in ten countries, analysing its positive and negative impact on society's behavior regarding the origin, symptoms, and prevention of SARS-CoV-2.Methods: A comprehensive narrative analysis of available data was conducted to evaluate societal and resilience responses during the COVID-19 pandemic. The study consulted academic and grey literature, from February 1, 2020, to March 1, 2022, focusing on ten countries that exhibited heterogenous responses to pandemic, including EU (Italy, Denmark, Sweden, Spain, Portugal, Romania, France, and Germany) and non-EU (United Kingdom and Israel) countries.Results: The stringency of policy responses varied between countries and over time, with some countries implementing strict lockdowns while others only issued recommendations. Vaccination campaign and the spread of less virulent variants of the virus has led most countries to lift most restrictions by April 2022. However, vaccine uptake and refusal remain complex issues influenced by social norms, cultural beliefs, access to information, and trust in government authorities. Social media played a significant role during the pandemic, but healthcare professionals’ active participation in addressing misinformation was lacking.Conclusions: The COVID-19 pandemic highlighted the importance of Public Health in developing proper strategies and utilizing digitals tools to counteract infodemic and spread relevant information. Healthcare workers should improve their communication skills to face future epidemics and be trusted by the population. Social media and digital platforms should be studied and used effectively in times of emergency.